Immigration and the Constraints of Justice : Between Open Borders and Absolute Sovereignty. - Pevnick, Ryan (Cambridge University Press, 2011)
Explores the constraints justice imposes on immigration policy, identifying claims citizens make of their states and how outsiders are excluded.